Effects of mineral trioxide aggregate, BiodentineTM and calcium hydroxide on viability, proliferation, migration and differentiation of stem cells from human exfoliated deciduous teeth - Leandro Borges Araújo; Leopoldo Cosme-Silva; Ana Paula Fernandes; Thais Marchini de Oliveira; Bruno das Neves Cavalcanti; João Eduardo Gomes Filho; Vivien Thiemy Sakai (University of São Paulo, 2018)
Abstract Objective: The aim of the study was to evaluate the effects of the capping materials mineral trioxide aggregate (MTA), calcium hydroxide (CH) and BiodentineTM (BD) on stem cells from human exfoliated deciduous teeth (SHED) in vitro. Material and Methods: SHED were cultured for 1 - 7 days in medium conditioned by incubation with MTA, BD or CH (1 mg/mL), and tested for viability (MTT assay) and proliferation (SRB assay). Also, the migration of serum-starved SHED towards conditioned media was assayed in companion plates, with 8 μm-pore-sized membranes, for 24 h. Gene expression of dentin matrix protein-1 (DMP-1) was evaluated by reverse-transcription polymerase chain reaction. Regular culture medium with 10% FBS (without conditioning) and culture medium supplemented with 20% FBS were used as controls. Results: MTA, CH and BD conditioned media maintained cell viability and allowed continuous SHED proliferation, with CH conditioned medium causing the highest positive effect on proliferation at the end of the treatment period (compared with BD and MTA) (p<0.05). In contrast, we observed increased SHED migration towards BD and MTA conditioned media (compared with CH) (p<0.05). A greater amount of DMP-1 gene was expressed in MTA group compared with the other groups from day 7 up to day 21. Conclusion: Our results show that the three capping materials are biocompatible, maintain viability and stimulate proliferation, migration and differentiation in a key dental stem cell population.